2019
DOI: 10.1108/gs-01-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of healthcare service quality factors using grey relational analysis in a dialysis center

Abstract: Purpose The purpose of this paper is to investigate the relative influences of technical and functional quality levels of service quality and patient satisfaction. In this context, the healthcare service quality and the factors affecting customer satisfaction were evaluated using the grey relational analysis (GRA) method. Design/methodology/approach This is a survey-based study which involves 15 patients in a dialysis center, so the GRA is applied to clarify the uncertainty on service quality level with a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Sassere et al observed that service quality includes two parts, the service results and the method of providing services [45]. Roca et al held a view that service quality is intimately correlated with confirmation and, thereby, the perceived usefulness of online education [46].…”
Section: Hypothesis 3 (H3) Ss Interaction Has a Positive Effect On Sc Interactionmentioning
confidence: 99%
“…Sassere et al observed that service quality includes two parts, the service results and the method of providing services [45]. Roca et al held a view that service quality is intimately correlated with confirmation and, thereby, the perceived usefulness of online education [46].…”
Section: Hypothesis 3 (H3) Ss Interaction Has a Positive Effect On Sc Interactionmentioning
confidence: 99%
“…The key areas of Grey System Theory include grey relational analysis, grey generating space, grey forecasting, grey decision making, grey control, and grey mathematics. Grey System Theory has seen application in numerous fields, including agriculture (Tan et al, 2014), supplier selection (Mahmoudi et al, 2021a), economic growth analysis (Huang et al, 2020), health care management (Aydemir & Sahin, 2019;Javed and Liu., 2018), sustainable development (Ikram et al, 2021;Abid et al, 2021), environment (Hao et al, 2006), electromagnetic data processing (Jiang et al, 2017), traffic flow prediction (Xiao et al, 2020), energy and emissions (Chen et al, 2021;Zhu et al, 2019), project management (Sheikh et al, 2019;Javed & Liu, 2019), machine learning (Xie et al, 2021;Ma, 2019), among others. It can be seen that the application of Grey System Theory is widespread and multi-disciplinary.…”
Section: Soil and Water Conservation (T9)mentioning
confidence: 99%
“…An essential approach of the grey system theory (GST) used in the decision-making process and measuring the changes of similarities and differences between its factors over time is called Grey Relational Analysis (GRA) (Feng and Wang, 2000;Aydemir et al, 2013). This method is used in the elimination and analysis of ambiguous relationships between criteria and options, examination of integrated circuit marking process (Jiang et al, 2002), restoration planning of power distribution systems (Chen et al, 2005), recruitment decisions (Olson and Wu, 2006), damage assessment (He and Hwang, 2007), a causal decision-making model (Tseng, 2009), determination of critical path through a network (Zhongmin and Xizu, 2009), supplier selection (Yang and Chen, 2006;Özdemir and Deste, 2009;Zavadskas et al, 2010;Hashemi et al, 2015;Cakir and Akel, 2017), stock market forecasts and portfolio selection (Huang and Jane, 2009), optimization of turning parameters (Yilmaz and Gungor, 2010;Ramesh et al, 2016;Prakash et al, 2020;Lakshmanan et al, 2021), evaluation of e-commerce system security (Liu, 2011), ergonomics (Akay, 2011), evaluation of the performance of enterprises (Tayyar et al, 2014;Aydemir and Sahin, 2019), risk and quality analysis (Baynal et al, 2018;Yazdani et al, 2019), product analysis (Chan and Tong, 2007;Sahin and Aydemir, 2019), and social networks (Weng et al, 2021).…”
Section: Grey Relational Analysis (Gra)mentioning
confidence: 99%